Genetic architecture behind developmental and seasonal control of tree growth and wood properties in Norway spruce - Chen, Zhi-Qiang; Zan, Yanjun; Zhou, Linghua; Karlsson, Bo; Tuominen, Hannele; García-Gil, Maria Rosario; Wu, Harry X. (Frontiers in Plant Science, 2022)
Genetic control of tree growth and wood formation varies depending on the age of the tree and the time of the year. Single-locus, multi-locus, and multitrait genome-wide association studies (GWAS) were conducted on 34 growth and wood property traits in 1303 Norway spruce individuals using exome capture to cover ~130K single nucleotide polymorphisms (SNPs). GWAS identified associations to the different wood traits in a total of 85 gene models, and several of these were validated in a population of the mother trees. A multi-locus GWAS model identified more SNPs associated with the studied traits than single-locus or multivariate models. Changes in tree age and annual season influenced the genetic architecture of growth and wood properties in unique ways, manifested by non-overlapping SNP loci. In addition to completely novel candidate genes, SNPs were located in genes previously associated with wood formation, such as cellulose synthases and a NAC transcription factor, but that have not been earlier linked to seasonal or age-dependent regulation of wood properties. Interestingly, SNPs associated with the width of the year rings were identified in homologs of Arabidopsis thaliana BARELY ANY MERISTEM 1 and rice BIG GRAIN 1 which have been previously shown to control cell division and biomass production. The results provide tools for future Norway spruce breeding and functional studies.